2015
DOI: 10.1245/s10434-015-4686-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Oncological and Functional Outcomes Between Primary Whole-Gland Cryoablation and High-Intensity Focused Ultrasound for Localized Prostate Cancer

Abstract: In this study, both primary whole-gland cryoablation and HIFU demonstrated good oncological outcomes for localized prostate cancer. We validated the safety of the two treatment modalities and identified the importance of combined HIFU and transurethral resection of the prostate. The HIFU patients experienced better urinary function improvement and more possible sexual function preservation than the cryoablation patients; therefore, HIFU may provide better quality of life for patients with localized prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…If preoperative prostate volume was <30 mL, TURP and HIFU would be performed simultaneously. If preoperative prostate volume was ≥30 mL, HIFU would be performed 4 weeks later after TURP (Liu and Chiang 2016). …”
Section: Methodsmentioning
confidence: 99%
“…If preoperative prostate volume was <30 mL, TURP and HIFU would be performed simultaneously. If preoperative prostate volume was ≥30 mL, HIFU would be performed 4 weeks later after TURP (Liu and Chiang 2016). …”
Section: Methodsmentioning
confidence: 99%
“…In 2-year follow-up, Liu et al reported that both primary whole-gland cryoablation and HIFU demonstrated good oncological outcomes for localized prostate cancer. The HIFU patients experienced better urinary function improvement and more possible sexual function preservation than the cryoablation patients (17). They also identified the D'Amico high-risk group, postoperative PSA nadir >0.3 ng/ml and time to PSA nadir <3 months as predictors for biochemical recurrence after primary whole-gland prostate cryoablation (18).…”
Section: Introductionmentioning
confidence: 97%
“…Of 222 studies initially identified on 2 February 2017, 17 studies met the inclusion criteria after removal of duplicates, non-English language, reviews, letters, case reports, non-human studies and non-full text articles (figure 1) [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] . Three papers were excluded after full text examination as WG and focal cryotherapy were amalgamated.…”
Section: Search Resultsmentioning
confidence: 99%
“…Focal PT, VTP and IRE appeared to cause very little change from baseline though the men in these studies tended to have low volume lesions. The lack of randomized studies means intermodality comparison is difficult though from Li et al's and Liu et al's nonrandomized comparative studies, it would appear that WG HIFU is associated better EF than both focal and WG cryotherapy 28,30 . ED after HIFU is likely to result from heat dissemination to the surrounding cavernosal nerves and accessory or aberrant pudendal arteries found in up to 75% of men 28,39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation